Compositional control of pore geometry in multivariate metal–organic frameworks: an experimental and computational study. Issue 10 (14th December 2015) - Cadman, Laura K.; Bristow, Jessica K.; Stubbs, Naomi E.; Tiana, Davide; Mahon, Mary F.; Walsh, Aron; Burrows, Andrew D.
Abstract : Changing the ratio of the dicarboxylates, L : L′, in MOFs of the general formula [Zn2 (L)2– x (L′) x (dabco)] affords control of the pore geometry, through non-covalent interactions between the ligands. Abstract : A new approach is reported for tailoring the pore geometry in five series of multivariate metal–organic frameworks (MOFs) based on the structure [Zn2 (bdc)2 (dabco)] (bdc = 1, 4-benzenedicarboxylate, dabco = 1, 8-diazabicyclooctane), DMOF-1. A doping procedure has been adopted to form series of MOFs containing varying linker ratios. The series under investigation are [Zn2 (bdc)2– x (bdc-Br) x (dabco)]· n DMF1 (bdc-Br = 2-bromo-1, 4-benzenedicarboxylate), [Zn2 (bdc)2– x (bdc-I) x (dabco)]· n DMF2 (bdc-I = 2-iodo-1, 4-benzenedicarboxylate), [Zn2 (bdc)2– x (bdc-NO2 ) x (dabco)]· n DMF3 (bdc-NO2 = 2-nitro-1, 4-benzenedicarboxylate), [Zn2 (bdc)2– x (bdc-NH2 ) x (dabco)]· n DMF4 (bdc-NH2 = 2-amino-1, 4-benzenedicarboxylate) and [Zn2 (bdc-Br)2– x (bdc-I) x (dabco)]· n DMF5 . Series1–3 demonstrate a functionality-dependent pore geometry transition from the square, open pores of DMOF-1 to rhomboidal, narrow pores with increasing proportion of the 2-substituted bdc linker, with the rhomboidal-pore MOFs also showing a temperature-dependent phase change. In contrast, all members of series4 and5 have uniform pore geometries. In series4 this is a square pore topology, whilst series5 exhibits the rhomboidal pore form. Computational analyses reveal that the pore size and shape in systems1 and2 is altered through non-covalent interactions between the organic linkers within the framework, and that this can be controlled by the ligand functionality and ratio. This approach affords the potential to tailor pore geometry and shape within MOFs through judicious choice of ligand ratios.